Electrolytes Containing Triethyl Phosphate Solubilized Lithium Nitrate for Improved Silicon Anode Performance - Rynearson, Leah; Rodrigo, Nuwanthi D.; Jayawardana, Chamithri; Lucht, Brett L. (Journal of the Electrochemical Society, 2022)
An electrolyte consisting of lithium nitrate (LiNO 3 ) and lithium difluoro(oxalato)borate (LiDFOB) in ethylene carbonate (EC), ethylmethyl carbonate (EMC), and triethyl phosphate (TEP) is used to improve the long-term cycling stability of silicon anodes. TEP was selected for its ability to dissolve LiNO 3 in carbonates to a concentration of ∼0.2 M. The large amount of LiNO 3 combined with the LiDFOB salt leads to a capacity retention of 87.1% after one hundred cycles due to the formation of a relatively stable solid electrolyte interphase (SEI). Ex-situ surface analysis reveals that the SEI consists of oxalates, lithium alkyl carbonates, borates, and nitrate reduction products. By selecting two components which are preferentially reduced (LiNO 3 and LiDFOB), the SEI is able to inhibit continuous solvent decomposition and allows for improved electrochemical cycling for pure silicon anodes.